LiveGene conversations on livestock genetics for development: African Chicken Genetic Gains Project - International Livestock Research Institute (International Livestock Research Institute, 2016)
LiveGene conversations on livestock genetics for development interview with Gabrielle Persley talking to Tadelle Dessie and Olivier Hanotte about the African Chicken Genetic Gains Project. Recorded in December 2015.